Estratégias de cultivo para a produção de polissacarídeo capsular por Haemophilus influenzae tipo b e determinação de parâmetros de qualidade para o produto - Silva, Mateus Ribeiro da (2010)
Haemophilus influenzae type b (Hib) is a Gram negative bacterium responsible for causing meningitis worldwide. The capsular polysaccharide b, a polymer composed by repeating units of ribosyl-ribitol phosphate (PRP), is the major virulence factor and it is used in the formulation of the vaccine against this microorganism. Despite their high efficiency, the conjugated vaccine against Hib is a product of high production cost, which involves fermentation, purification and conjugation processes to obtain a final product within the specifications of the World Health Organization (WHO). The improvement of the culture medium and cultivation conditions can contribute to reduce the cost of this vaccine in order to facilitate its dissemination in developing countries. The main objective of this work was to identify culture conditions that result in higher production of capsular polysaccharide, helping to reduce costs in the steps of purification and conjugation. The experiments were carried out in shake flasks or in bioreactors with 7-13 liters of capacity. The temperature was maintained at 37 °C, pH controlled at 7.5 by adding NaOH 5M and the concentration of dissolved oxygen (CDO) maintained at 30% of air saturation. The specific flow rate of air ranged between 0.2 and 1 VVM. Samples were collected at regular time intervals to measure optical density (DO540nm), biomass concentration, capsular polysaccharide (PRP) production and concentrations of glucose and metabolites. Two possibilities for increasing polysaccharide production were studied: 1) different strategies of fed-batch cultivation consisting of: a) intermittent addition of glucose (FBIG), b) constant feeding (FBCF), c) exponential feeding (FBEF), e d) exponential feeding with cell recycle and perfusion (FBER + P); 2) improvement of culture media composition regarding the carbon/nitrogen ratio through the use of central composite rotational design (CCRD) methodology, having as independent variables: Soy Peptone (S), Yeast Extract (YE) and Glucose (G). Quality parameters were also evaluated to assess the molecular weight profile of the product (PRP) as well as morphological aspects of the microorganism. Economic analysis of different cultivation strategies was used to identify the more economically viable process. The results of the different cultivation strategies together with the outputs of the studied processes cost analysis showed that FBCF, with a cost of U.S.$ 425.50/g PRP and productivity of 88 mg/L.h, showed to be the best alternative among PRP production processes due to its lower cost with a good productivity. In the study of the culture media composition through the statistical analysis of the CCRD results showed that the best culture media composition (BCM) consisted of S 5 g/L; YE 5.5g /L and G of 15.25 g/L. DO540nm and PRP volumetric production values of 8.4 and 410 mg/L, respectively, were attained in validation experiments carried out in shake flasks at the BCM condition. For the bioreactor BCM validation experiment, biomass concentration of 3 g DW/L and polysaccharide production of 600 mg PRP/L were observed. Similar values were reached at validation runs performed in shake flasks and bioreactor for the central point CP condition, showing that both BCM and CP conditions belong to the optimum region. The analysis of quality parameters showed that the cultivation time influences strongly the size of the polysaccharide molecule. The longer the cultivation time, the lower molecular weight was found. The analysis by transmission electron microscopy (TEM) of H. influenzae cells revealed a predominance of round cells in the sixth hour of cultivation, whereas in the twelfth hour of cultivation the cells exhibited a more elongated morphology with the presence of cytoplasmic inclusions in the shape of granules, possibly due to the accumulation of some reserve material. Based on these results, the new composition of the culture medium resulted in an increased of cell growth and capsular polysaccharide production with half of the sources nitrogen (soybean peptone and yeast extract) concentrations, which reduces the production cost. The cultivations that resulted in higher production and productivity of polysaccharide were FBCF (1600 mg PRP/L and 88 mg PRP/(L.h)) and FBER+ P (1800 mg PRP/L and 129 mg PRP/(L.h)). The FBER+P reached 30% higher productivity of polysaccharide than the best result described in the literature (90 mg PRP/(L.h)). However, the FBCF cultivation was economically more viable.